2015
DOI: 10.1097/sla.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Immunoenhancing Enteral and Parenteral Nutrition for Gastrointestinal Surgery

Abstract: This study suggests that IMEN outperformed other nutrition types for reducing complications and IMEN should be considered the best available option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…Optimal timing of the immunonutritional intervention may be important. Generally, preoperative immunonutritional intervention is thought to be beneficial for patients undergoing GI surgery [25]. However, no available studies have discussed when to initiate and for how long to maintain an immunonutritional intervention for patients receiving pCRT for the treatment of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal timing of the immunonutritional intervention may be important. Generally, preoperative immunonutritional intervention is thought to be beneficial for patients undergoing GI surgery [25]. However, no available studies have discussed when to initiate and for how long to maintain an immunonutritional intervention for patients receiving pCRT for the treatment of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, even if ERAS is nowadays a standard of care in the institution where the present analysis was conducted, the perioperative care pathway was not yet standardized at the time of trial initiation. The beneficial effect of preoperative nutritional support on postoperative outcome has been widely investigated and is strongly recommended in major abdominal surgeries [1] . The present results suggest close nutritional follow-up beyond the postoperative phase, especially when confronted with postoperative complications, and need to be considered an argument for appropriate nutritional care and follow-up even within an ERAS program.…”
Section: Discussionmentioning
confidence: 99%
“…Then, energy and protein gaps were calculated by comparing effective energy and protein intake with energy and protein needs. Appetite and food intake compared to the situation before the illness occurred (baseline food intake) were assessed with a visual analogue scale (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Pre-and Postoperative Evaluation Of Nutritional Risk and Nutmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that preoperative nutritional intervention may reduce the incidence of postoperative morbidities (16,17). However, no studies to date showed that these nutritional interventions could improve long-term outcomes after esophagectomy.…”
mentioning
confidence: 99%